Aspects Concerning Tax Evasion in Alba County and Brașov Region - Radu, Claudia Florina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
One of the effects of evasion is the reduction in tax revenues, so the state will have less money to supply public goods and services. Instead, if there are sustained efforts to reduce tax evasion, revenues to the budget will increase, will exist resources to counter the economic crisis and for providing public services to citizens: education, health, social security, etc. Additional money obtained from reducing tax evasion would solve many of the problems related to the lack of resources facing states today. That is why it is so important to combat and reduce tax evasion, both nationally and globally. Starting from the analysis of some data about tax audit and budget revenues of Alba County, we highlighted the main factors that determine people to pay taxes: firstly, the positive incentives, then the fear of negative consequences of non-payment, and, to a small extent, the moral factors.